Matematik adalah nukleus kepada sains hakiki, kata sarjana pelawat - Universiti Putra Malaysia, Bahagian Komunikasi Korporat (Universiti Putra Malaysia, 2013)
SERDANG, 17 April (UPM) – Mathematics is like the nucleus for the other “hard” sciences to revolve, says a visiting don from the University of Auckland, New Zealand.